Performance of Boer and their Crossbreed Goats in Nepal - A Review - Parajuli, S. (International Journal of Environment, Agriculture and Biotechnology, 2020)
There are about 10.25 million goats in Nepal. Most of these are local and adaptive to different ecological zones of Nepal. Despite of big goat population, performance in terms of daily gains were very low as compared to the Boer crossbreeds. The crossbreed Boer goat is a remarkable small-stock ruminant that possesses distinctive qualities enabling it to excel as an efficient production performer. The Boer goats had faster growth rates and were heavier than the indigenous breeds of goats from Nepal. The daily gain of Boer is 80-140 gm/day and Boer crossbreeds is 100-200 gm/day varying with different blood level of Boer crossbreeds. It is early maturing, reaching a mean maximum weight ≈ 62 kg at 3.5 years of age on natural pasture under extensive grazing conditions. Twinning percentage is about 40-50% in the crossbreeds. The indigenous goats of Nepal are subjected to crossbreeding with Boer goats in order to utilize the Boer goat breed as an alternate breed for production and reproduction performances. Boer milk is rich in fat followed by lactose and protein. Dressing percentage is about 56-60 % at the age of full teeth placement. They are resistant to various disease due to better performance of adrenal cortex and high cortisol production. Mortality rate is more for quadruplet and triplet kids. They are the best browsers and used as a controller in bush encroachment. Flexibility in acclimatization and other vital characteristics signified better performance of Boer and their crossbreeds in diverse country like Nepal.